ANALISIS PEMBELAJARAN MATEMATIKA PADA SEKOLAH DASAR YANG MENERAPKAN PENDEKATAN PMRI DAN SEKOLAH DASAR YANG TIDAK MENERAPKAN PENDEKATAN PMRI DI KOTA YOGYAKARTA - NEGARA, HASAN SASTRA (Universitas Islam Negeri Raden Intan Lampung, 2014)
The aims of this study were describing the process of mathematics learning and its problem solving for primary III students whom school was applying PMRI approach and non applying PMRI approach (Realistic Mathematics Education in Indonesia). This research was a qualitative case study type. The subject of this study divided into 2, which were: subject for searching information about learning process and subject for searching information about problem solving. Subject in this study were 2 primary teachers, 1 teacher from SD “A” Demangan Baru and 1 teacher from SD “B” Demangan, another subject were 4 students, 2 students from SD “A” Demangan Baru and 2 students from SD “B” Demangan. The data was divided into 2, which were learning process data that contain about teacher and student activities in learning and mathematical problem solving data that contain about information problem solving in mathematics. Learning process data was collected from recording transcription result of learning activities toward two observations, while mathematical problem solving data was collected by using the think aloud method. The results revealed that the teaching and learning process at the school which apply PMRI approach began with providing contextual problems. The student do mathematical mathematization even though with simple language and symbols. Students construct their own knowledge and teacher was as the facilitator. However, the process of interweaving one material to another was still not observed yet. In the process of teaching and learning at non-PMRI school, teacher began the teaching and learning process by explaining homework. There was no activity of solving problems in group. Students solved a problem by using the way that their teacher teaches them and the skill was developed based on the example and exercises. The problem solving skill of students who have high ability at school which applied PMRI approach was better than that of students who have high ability at school which did not apply PMRI approach. However, the problem solving skill of students who have low ability at school which applied PMRI approach is not better than that of students who have low ability at school which did not apply PMRI approach